BRAIN MORPHOLOGY STRUCTURE AND FUNCTION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The brain is one of the most complex and important structures in the human body. It is responsible for all physiological and psychological processes, including perception, thinking, memory, emotions, and movement control. The brain is made up of two main types of tissues: Gray matter – includes neurons, their bodies, and dendrites. It is mainly responsible for the processing and transmission of information. White matter consists mainly of axons of neurons covered with myelin, which accelerates the transmission of nerve impulses. Gray and white matter are found in different parts of the brain: Gray matter is located in the cerebral cortex (cerebral cortex). White matter is located deeper and consists of long nerve fibers that transmit signals between different parts of the brain.